2016
DOI: 10.20965/ijat.2016.p0079
|View full text |Cite
|
Sign up to set email alerts
|

Development of Heating and Cooling Injection Mold with Far-Infrared Radiation Heater

Abstract: Several rapid heating and cooling molding methods have been developed for practical use to improve the surface quality of plastic injection-molded products. These methods, however, need expensive equipment and complex molds that require vast know-how, and hence cannot be applied easily to actual production. In order to establish a molding method in which the mold’s cavity surfaces can easily be heated, we designed and manufactured a heating and cooling injection mold with a far-infrared radiation heater.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The results of our previous study on the measurement of the temperature distribution of a melt flowing in a mold (11) revealed that the temperature in the vicinity of the cavity wall increases with increasing heating cylinder temperature, mold temperature, and injection rate. Furthermore, the results of another previous study on heat-and-cool injection molding (12) demonstrated that the increase in the temperature of a polymer in the vicinity of a cavity wall increases the adhesion between the polymer and the cavity wall. Therefore, our assumption is considered to be valid.…”
Section: Effect Of Molding Conditions On Demolding Resistancementioning
confidence: 94%
“…The results of our previous study on the measurement of the temperature distribution of a melt flowing in a mold (11) revealed that the temperature in the vicinity of the cavity wall increases with increasing heating cylinder temperature, mold temperature, and injection rate. Furthermore, the results of another previous study on heat-and-cool injection molding (12) demonstrated that the increase in the temperature of a polymer in the vicinity of a cavity wall increases the adhesion between the polymer and the cavity wall. Therefore, our assumption is considered to be valid.…”
Section: Effect Of Molding Conditions On Demolding Resistancementioning
confidence: 94%
“…Some of the authors of this paper have proposed a heating and cooling injection mold that can be easily heated using a far-infrared radiation heater and a three-dimensional cavity plate. The effects of heating the mold cavity surface on the appearance of molded products composed of fiber-reinforced thermoplastics have been examined using this mold [37,38]. Since an infrared radiation heater is often used to heat the sheets in overmolding, we speculated as to whether it would be possible to heat both the sheet and the mold surface simultaneously using only one far-infrared radiation heater.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been proposed in the literature to modulate the cavity temperature during the process, such as introduction of radiation sources, induction coils, and proximity heating. The induction heating is realized by introducing a cavity insert wound with induction coils, which allows temperature modulation [14]. The radiation heating is based on the introduction of a movable insert that can be heated by an infrared source [8].…”
Section: Introductionmentioning
confidence: 99%